Pengaruh Terapi Relaksasi Dzikir Terhadap Tingkat Kecemasan Pada Lansia Di Masa Pandemi COVID-19 Di KP Tipar Desa Hegarmanah Tahun 2021: The Effect of Dhikr Relaxation Therapy on Anxiety Levels in the Elderly During the COVID-19 Pandemic at KP Tipar Hegarmanah Village in 2021 - N Siska Adrianty P (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: COVID-19 (SARS-CoV-2) is an infectious disease caused by a type of Corona Virus that has been found. This creates anxiety in many circles. In the United States, are aged 65 years and over, and more than 60% of May 20, 2020. For Indonesia, the age group that died the highest was the age group of > 60 years old (elderly) which is as much as 44%. An elderly person is someone who is 60 years of age or older. Handling anxiety needs to use a holistic approach (comprehensive). Dhikr therapy has a positive impact on cognitive, affective, and spiritual aspects. Methods: This research uses this type of quantitative research. This type of research is experimental quasi research through a pre-experimental design approach (Trial) with a pre-post-test design in one group of One Group pre-post-test design. The feature of this study is to uncover a causal relationship by involving one group of subjects. The subject group was observed before the intervention and was then observed again after the intervention. Where in the early stages of anxiety. Results: The results of the Wilcoxon Test can be concluded that the research data has an influence. Based on this, the researchers looked at the overall test results of test statistics output. The p-value in asym-sig is obtained 0,000 < 0,05. Discussion: The conclusion is that there is an effect of dhikr relaxation therapy on the level of anxiety in the elderly during the COVID-19 pandemic at KP Tipar Hegarmanah Village in 2021.